Significance of nutrient fluxes via submarine groundwater discharge in the Bay of Puck, southern Baltic Sea - Beata Szymczycha (Oceanologia, 2020)
Summary: In this study, we collected submarine groundwater discharge (SGD) and seawater samples at six sites in the Bay of Puck, in the southern Baltic Sea, in order to estimate the nutrient distribution in groundwater affected areas. In addition, we estimated nutrient fluxes via SGD, including both fresh SGD (FSGD) and recirculated seawater SGD (RSGD), to the entire Bay of Puck. Phosphate (PO43−) concentrations varied significantly among study sites and seasons, while both ammonium (NH4+) and nitrates (NO3−) concentrations varied only seasonally. The N:P ratio indicated P limitation in most of the samples. The estimated seasonal and annual loads, via SGD, of both dissolved inorganic nitrogen (DIN; 9303 t yr−1) and PO43− (950 t yr−1), were the most significant source of nutrients to the Bay of Puck, and notably higher than quantified before (FSGD nutrient loads of 50 t yr−1 and 56 t yr−1 for DIN and PO43−, respectively). The SGD fluxes reported here indicate some of the highest rates of sediment-water fluxes reported in the Baltic Sea. These results suggest that SGD (both FSGD and RSGD) should be considered as source of chemical substances to the marine environment. Keywords: Biogeochemistry, SGD, Coastal zones, Return flux, Nitrogen, Phosphorous, Bay of Puck (Baltic Sea)